2016
DOI: 10.1080/09064710.2016.1197307
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing fertilizers doses and their effects on photosynthesis and biomass yield ofHibiscus cannabinuscultivated on BRIS soil

Abstract: In tropical climate, huge amount of fertilizer need to be used for the cultivation of kenaf (Hibiscus cannabinus L.) in Beach Ridges Interspersed with Swales (BRIS) soil, however this approach is not cost effective and environmental friendly. Therefore, the optimizing of fertilizer rate for BRIS soils and selection of suitable soil amendments are crucial to get a higher yield. In this study, the effects of different combinations of urea, chicken manure and biochar on soil properties, growth performance and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Typically, BRIS soil has acidic soil property less than pH five, as analysed by Toriman et al (2009). Although BRIS soil properties have many drawbacks, the research on BRIS soil fertility status in Malaysia on chilli and tomato (Zaharah et al 1992), acacia (Shariff et al 1993;Shariff & Kadir 1994), vegetable crops (Jahan et al 2014), paddy (Lah et al 2011), kenaf (Abdul-Hamid et al 2009Hossain et al 2011;Malisa et al 2011;Yusoff et al 2011;Basri et al 2016;Halimatul et al 2017), pineapple (Arshad et al 2011;Arshad & Armanto 2012), sweet potato (Ishaq et al 2014b), corn (Ishaq et al 2014a;Arshad et al 2015b), okra (Khandaker et al 2017), watermelon (Tahir et al 2018), roselle (Arshad et al 2015a;Norhayati et al 2019;Zakaria et al 2019), and fig (Azmi et al, 2020) has been conducted since it has vast potential for agriculture and forestry use. Interestingly, it has many beneficial bacteria (Mustapha et al, 2017) for instance, entomopathogenic fungi (Elham et al, 2018) are reported in BRIS soil, thus improving soil fertility and plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, BRIS soil has acidic soil property less than pH five, as analysed by Toriman et al (2009). Although BRIS soil properties have many drawbacks, the research on BRIS soil fertility status in Malaysia on chilli and tomato (Zaharah et al 1992), acacia (Shariff et al 1993;Shariff & Kadir 1994), vegetable crops (Jahan et al 2014), paddy (Lah et al 2011), kenaf (Abdul-Hamid et al 2009Hossain et al 2011;Malisa et al 2011;Yusoff et al 2011;Basri et al 2016;Halimatul et al 2017), pineapple (Arshad et al 2011;Arshad & Armanto 2012), sweet potato (Ishaq et al 2014b), corn (Ishaq et al 2014a;Arshad et al 2015b), okra (Khandaker et al 2017), watermelon (Tahir et al 2018), roselle (Arshad et al 2015a;Norhayati et al 2019;Zakaria et al 2019), and fig (Azmi et al, 2020) has been conducted since it has vast potential for agriculture and forestry use. Interestingly, it has many beneficial bacteria (Mustapha et al, 2017) for instance, entomopathogenic fungi (Elham et al, 2018) are reported in BRIS soil, thus improving soil fertility and plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…The rest is core fibers with higher lignin content and much shorter than bast fibers [3]. Kenaf bast fibers are cellulose-rich, thus, they are attractive substitute raw material for pulp and paper production [4]. Interest in new hybrid materials of fibers coated conductive polymers has great attention in recent years due to its functional properties that produced good mechanical properties with high electrical conductivity level [5].…”
Section: Introductionmentioning
confidence: 99%